Isolated CNS relapse in FLT 3 mutation positive CMML post allogeneic stem cell transplant: Report of a rare case - Deepti Mutreja; Shipra Verma; S Venkatesan; Sanjeevan Sharma; Satyaranjan Das (Wolters Kluwer Medknow Publications, 2021)
Chronic myelomonocytic leukemia is a clonal chronic hematopoietic disorder that has been classified under the category of Myelodysplastic syndrome/Myeloproliferative neoplasms (MDS/MPN). CMML has high chances of transforming to acute leukemia, however isolated CNS relapse in CMML has never been reported in literature. We report an extremely rare case of a 47 yearold female diagnosed to have CMML- 2 in remission, who developed an isolated central nervous system relapse after matched related allogeneic hematopoietic stem cell transplantation. To our knowledge this is the first report of isolated CNS relapse in CMML post allogeneic stem cell transplant.